Open resilience : application of a geo-analytics platform using free and open source software towards resilient land use planning. - Gasgonia, Francis Josef C. (School of Urban and Regional Planning, University of the Philippines Diliman, 2023)
The identification of critical infrastructure facilities is critical for climate and disaster risk assessments that forms part of a resilient land use plan. This study utilized the application of a geo-analytics platform using free and open source software for geo-analytics, namely Quantum GIS (QGIS) in generating multi-hazard exposure maps of critical infrastructure facilities in Taguig City, Philippines. The study was conducted as a necessity for planners looking for an alternative viable solution for resilient land use planning using non-proprietary Geographic Information Systems (GIS). The study developed a workflow for geospatial analysis with direct application in hazard exposure mapping for floods, active fault lines, and waterway easements. A review of open data portals was first performed which discussed the limitations and opportunities of existing official data repositories. A supplementary online survey was likewise conducted with local planners to understand their knowledge, skills, attitudes, and perceptions to GIS and its application to disaster risk assessment. The survey responses from local planning and development offices showed that they are open to improving institutional capacity and professional capabilities in GIS, particularly in QGIS. A comparative review of different spatial decision support systems for climate and disaster risk assessment was also carried out that revealed important ways forward in further developing open tools for disaster risk assessment. The case study was able to identify the multi-hazards exposure profile of Taguig City using open data while using the free and open-source software QGIS. The data used were accessed from online data portals that have free public access, and data formats useful for independent study. The online survey also provided invaluable insights into the knowledge, skills, awareness, perceptions, and preferences of the respondents with regards to GIS-related topics. The results of the survey showed that there is a need for GIS training programs and in particular an expressed openness to learning QGIS. Also, the review of existing spatial decision support systems available in online and standalone platforms showcase the limitations and opportunities of adapting graphical models to automate the process of disaster risk assessments. The study was able to demonstrate a viable alternative geo-analytics platform using free and open-source software for geographic information systems and open data. Results of the comparative review of existing data portals and spatial decision support systems helped in the development of the proposed open resilience framework. Said framework was able to produce the required exposure maps of critical infrastructure in Taguig City. In order to support proposed open resilience framework, the results of the study recommend that a capability building program centered on Free and Open Source Software for Geospatial (FOSS4G) applications with modules for disaster risk assessment should be developed and offered to environmental planners or other personnel in the local planning and development offices or their counterparts in the local disaster risk management offices. In addition, the review of open data and data portals shows room for improvement in opening data for disaster risk managements. Open access to this information promotes transparency, innovation, and the capacity of more users in the disaster risk reduction and humanitarian action community for independent analysis.